Systems study on the operations of Daizuki Tube Ice - Sotyco, Russell Ian (Animo Repository, 2022)
This paper studied Daizuki Tube Ice, a company that has been operating for around 5 years. Although the company has become a business that is profitable, it still faces issues and problems that need to be resolved and areas to be improved. To be able to resolve this, this paper took an in-depth look on the operations and current situation of the company. Using the data available from 2015, the paper looked into the different strengths, weaknesses, opportunities, and threats of the company. It also proposed and implemented solutions to the problems faced by the company. The paper has identified that the most pressing problem of the company is that waiting times for the company’s customers reached more than two hours costing the company significant sales opportunities. An initial 4-M Ishikawa diagram was made categorizing the probable causes of the extended waiting times. The final causes were validated and found to be contributing to the problem. The main cause of the long queue is the unavailability of the tube ice which is in turn is caused by a variety of causes. First of which is the that the company’s machines are not only inefficient but are being underutilized. It is clear that the machines are capable of producing more but because of the limited storage space, they are not continually being operated. If efficiency of machines is increased and theoretical capacity be reached, the per hour production should increase and more ice should be available for distribution. One of the causes of the inefficiency of machines is the build-up of scales. Similarly, because of the build-up of scales, machines are shut down once every month to give way to maintenance activities. Albeit not done simultaneously with all the machines, the decreased production results to longer waiting times for customers. Finally, the sudden surge of customers including dealers during certain times of the day contribute to the quick depletion of built-up inventory and thus the unavailability of the product. The paper has suggested a multi-approach solution to the company’s problem. This includes scheduling of bulk orders, purchase of an additional storage, improvement of efficiency and utilization of existing machines, and reduction of maintenance down times. In conjunction with all of these, is to improve the layout of the facility alongside proper personnel training. The final solutions that were decided upon was to purchase an additional container type storage. The reason for this is being that container type storage is readily available, it is also cheaper and more effective in keeping the ice frozen. Scheduling of bulk orders were also placed from 12AM-3AM. This should be the time when big distributors should get their ice from the plant. This essentially works as a buffer storage wherein the products are already given to the customers. The time was decided on the must that no other customers be present during this time. Additionally, the company wanted to provide as little incentive to the distributors as possible and to have more time before the peak time so as to give the production time to fill the storages. However, an alternative was proposed wherein the bulk orders would be done during 3AM-6AM. This alternative was previously a “No-Go” since there are other customers being assisted by the baggers during this time. The dealers suggested a work-around wherein the additional storage would be allocated entirely to them and they would position their own personnel to manage the storage as well as load their trucks. With this, the company need not allocate baggers for the dealers and as an added benefit for the company, the dealers have agreed that the meltage incentive no longer be given. It was also suggested that the company make use of a scale inhibitor to minimize the maintenance down times of the machines. Although it has a higher costs, this is offset by its ease of use, minimal intervention and minimal down times. With the scale inhibitor in place, efficiency of the machines would increase. It was also suggested to sell the small ice machine and further utilize the bigger and more efficient machines. This results to less manpower required for the company. All of the solutions were completed on the end of 2nd quarter of 2016. The actual benefits were a bit lower than the estimated ones as the solution suggested is not the one that was fully implemented. Nonetheless, the solutions implemented had a positive impact and was able to contribute additional sales that gave the company an additional profit of around Php1.2 Million.